Effect of Span Length on the Seismic Design Modification Factors of Steel Frames with High Ductility - Borhan, Nadhirah; Vafaei , Mohammadreza; C. Alih, Sophia (International Journal of Integrated Engineering, 2022)
Seismic design modification factors (SDMFs) control the estimated force and displacement to structures during seismic events. Seismic design codes recommend similar SDMFs for short and long-span structures. Therefore, this study investigated the effect of span length on the SDMFs of steel frames with high ductility. For this purpose, nine steel frames with three different span lengths of 5, 10, and 15 m were selected and designed according to the specifications of ASCE/SEI 7-16. The designed structures were single, double, and three-story frames. The obtained results showed that the values of response modification factor (R), overstrength factor (?), and deflection amplification factor (Cd) were increased as the span length was increased. Besides, an increase in the number of stories decreased the value of R and ?-factors. It was concluded that the inelastic displacement of long-span steel frames might be underestimated if the given Cd values in the seismic design code were used.